Efficacy of trans-cerebellar diameter/abdominal circumference ratio versus head circumference/abdominal circumference ratio in prediction of asymmetrical intrauterine growth retardation - Maryi, Silvin Sofia; D., Indirani; P. S., Vinothkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Determination of gestational age is an important step of pregnancy management and foetal development evaluation in obstetrics. Any error in this gestational age estimation results in prematurity or post maturity and in case if the expected date of delivery is not known, there is high chance of perinatal mortality in the near outcome. Hence it is important in achieving an uneventful gestation to have a sensitive, specific and age independent obstetric biometric parameter that stays constant throughout the gestation. Trans-cerebellar diameters (TCD)/ abdominal circumference (AC) ratio are reliable, constant predictors to assess the gestational age and to evaluate fetal growth. Aim was to compare the accuracy of TCD/ AC ratio with head circumference (HC)/ AC ratio in predicting asymmetrical IUGR. Methods: A prospective study was conducted over a period of one year on 100 clinically suspected IUGR pregnancies who were evaluated with BPD, HC, AC and FL along with TCD were measured for assessing the sonological gestational age. Two morphometric ratios-TCD/AC and HC/AC were calculated. Estimated fetal weight was calculated for all these pregnancies and its percentile was determined. Then those clinically suspected IUGR cases were followed up to delivery and post-delivery new Ballord score and CAN score (clinical assessment of nutritional status at birth) were calculated. Results: In the present study, the sensitivity, specificity, PPV, NPV and DA were 83.93%, 65.91%, 75.81%, 76.32% and 76% respectively for TCD/AC ratio versus respectively for HC/AC ratio in predicting IUGR. Conclusions: Both ratios were gestational age independent and can be used in detecting IUGR with good diagnostic accuracy. However, TCD/AC ratio had a better diagnostic validity and accuracy compared to HC/AC ratio in predicting asymmetric IUGR.